The Colonial Bastille : A History of Imprisonment in Vietnam, 1862-1940 - Zinoman, Peter, 1965- (Book collections on Project MUSE., 2001)
Peter Zinoman's original and insightful study focuses on the colonial prison system in French Indochina and its role in fostering modern political consciousness among the Vietnamese. Using prison memoirs, newspaper articles, and extensive archival records.